The Weakness of Hadith–Hadith in the Book of Ibn Majah from the Perspective of Nasir al-Din al-Albani - Moch. Sulthon Zakaria; Wika Fisepta Septa Tiari Diria Putri (Civiliza Publishing, 2026)
The study of the status of hadith and its categorization in a number of hadith books has always been a debate among scholars and experts in hadith, including related to the book of Sunan Ibn Majah. One of the hadith figures who often criticizes the books of hadith is Nasir al-Din al-Albani. One of his famous works entitled Da’if Sunan Ibn Majah contains hadiths that are considered weak according to al-Albani. This study examines al-Albani’s hadith assessment methodology and its comparative position vis-à-vis classical hadith scholarship, with specific reference to the book Sunan Ibn Majah. This study employs a qualitative comparative approach (comparative hadith analysis) to analyze al-Albani’s methodology in grading hadith as weak (da‘if), focusing on the methodological patterns he applies and how they compare with classical hadith scholars such as Ibn Hajar al-‘Asqalani and al-Dhahabi. The primary objective of this study is to examine al-Albani’s methodological framework, rather than merely determining the status of hadith. The results of the study show that al-Albani’s assessment methodology differs systematically from the approach taken by the majority of scholars, particularly in his application of sanad criticism criteria. Al-Albani tends to establish the status of hadith based primarily on textual-critical analysis without always providing an in-depth examination of narrator credibility (‘adl and dhabith) or cross-referencing with mutabi’ and shahid reports, which has led some scholars to contest the basis of his grading decisions.